National Evaluation of the Community Anti-Crime Program, 1979-1981 ([Verlag nicht ermittelbar], 1988)
The survey was designed to explore the thesis that effective prevention and control of crime requires a community-wide effort that involves law enforcement agencies, other elements of government, and the citizens in a coordinated attack on problems of crime. The data include information on program start-up, implementation, and the community itself, as well as information on the specific activities undertaken by the programs.